Pengetahuan dan Sikap Masyarakat dalam Pencegahan dan Pemberantasan Jentik Nyamuk Demam Berdarah Dengue (DBD) Di Jayaraga Garut - nina sumarni; Udin Rosidin; Witdiawati Witdiawati (Loka Litbang Kesehatan Pangandaran, 2019)
Abstract. Cases of dengue hemorrhagic fever (DHF) are still a threat in Indonesia, especially entering the rainy season, the number of sufferers usually tends to increase, this occurs due to the proliferation of Aedes aegypti mosquito breeding breed. Prevention and eradication of dengue fever must be the responsibility of all communities. Efforts that can be done by the community are to be able to play an active role in monitoring mosquito larvae. This study aims to identify the knowledge and attitudes of the community in the prevention and eradication of dengue mosquito larvae. The head of the family in Jayaraga Garut, 103 kk, the amount of total populations, the study time was October 2018. Aspect Research Results Respondents' knowledge of participation in prevention and eradication of dengue vector still had 8 respondents whose knowledge was lacking. Attitude, there are still 9 responses whose attitude is not good. Participation in doing 3M most of the people of Jayaraga have prevented the breeding of the Aedes aegypti mosquito larvae even though there are still respondents who did nothing. The conclusion is that there are still some respondents whose knowledge, attitudes and actions are not good or not good.